Parenting in a digital era: A narrative review - Fox, Celine; Robertson, Deirdre; Lunn, Pete (ESRI, 2025)
School-aged children and adolescents under 18 in Ireland spend more time online than ever before. ‘Digital technology’ is a broad term that refers to electronic devices like computers, smartphones, smart TVs and game consoles. These devices can connect to the internet and access various types of online content, including games, social media, streaming services and educational resources. While digital technologies offer numerous benefits, such as access to information, educational tools and social connection, they can also pose risks to the mental wellbeing of children and adolescents. Many governments, including Ireland’s, have introduced policies to protect children online. Knowing when and how digital technologies cause harm can guide the development of effective policies. This review summarises international research on the effect of digital technologies on school-aged children and adolescents. Findings are presented as follows: 1) the impact of digital technology on wellbeing; 2) the challenges of parenting in a digital era; and 3) public health and policy interventions to protect children and adolescents online. This review adopts a narrative approach to explore this topic. It includes a broad literature search from academic databases, grey literature and non-academic sources, ensuring a wide range of insights from various disciplines. Both academic and non-academic sources are critically appraised to provide a balanced and contextually relevant discussion that may inform future research, policy and practice. This review includes a total of 297 references. Notably, this is a rapidly evolving area, with new research publications and policy developments emerging daily. As such, while the review offers a current overview, it can be viewed as a snapshot of a continuously shifting landscape. The findings of this review are summarised below.